Internet addiction, digital support use, and self-regulation in EFL university students’ writing - Atik Umamah; Ika Hidayanti (Universitas Syiah Kuala, 2026)
The increasing prevalence of internet use among students, leading to internet addiction, has both positive and negative implications for EFL learning. Considering gender differences, this research identified internet addiction levels, the types and frequency of using digital support, and the use of self-regulation with digital support in academic writing. Additionally, it sought to measure the significant difference in internet addiction, use of digital support, and self-regulation with digital support across genders. It also measures the extent to which internet addiction and the use of digital resources correlate with self-regulation. The research involved sixty EFL university students from a private institution in Malang, Indonesia. Data were collected using an internet addiction survey and the Self-regulated Learning with Technology at the University (SRLTU) Questionnaire to assess students’ internet use, digital support, and self-regulation. Findings show that: 1) male and female students have high internet addiction; 2) digital support in writing is moderately used, with the internet and assessment tools being the most utilized; 3) self-regulation with digital support is moderate, focusing on superficial use and collaboration; 4) gender differences exist in internet addiction and self-regulation but not in digital support use; 5) self-regulation in writing significantly correlates with digital support, not internet addiction. These findings underscore the critical interplay between gender, digital tools, and self-regulation in L2 academic writing. The findings highlight the need for tailored instructional strategies to optimize digital support use to enhance students’ self-regulation, leading to improved academic writing performance.